Use of CA-125 Tests and Computed Tomographic Scans for Surveillance in Ovarian Cancer. Issue 11 (November 2016) - Esselen, Katharine M.; Cronin, Angel M.; Bixel, Kristin; Bookman, Michael A.; Burger, Robert A.; Cohn, David E.; Cristea, Mihaela; Griggs, Jennifer J.; Levenback, Charles F.; Mantia-Smaldone, Gina; Meyer, Larissa A.; Matulonis, Ursula A.; et al.
Abstract : (Abstracted from JAMA Oncol 2016; DOI: 10.1001/jamaoncol.2016.1842) Data from a clinical trial presented at the 2009 American Society of Clinical Oncology Annual Meeting and published in 2010 compared results among patients with ovarian cancer in clinical remission, who were randomized to either active surveillance with cancer antigen 125 (CA-125) testing or clinical observation. Findings from this trial demonstrated that routine surveillance with CA-125 testing increased use of chemotherapy and decreased patients' quality of life without improving survival.